Analisis Perkembangan Karakter Tokoh Utama pada Manga Totsuzen Papa Ni Natta Saikyou Doragon No Kosodate Nikki Karya Ameko Kaeruda: Kajian Psikologi Sastra - Ardyn, Tyas Mahardhika; Ristiawati, Tia; Fredy, Mochammad (NAWA: Journal of Japanese Studies, 2025)
This article aims to reveal the personality dynamics and character development of the main character, Olivia in the manga Totsuzen Papa Ni Natta Saikyou Doragon No Kosodate Nikki. The study adopts a literary psychology paradigm and employing a descriptive qualitative method. Data collection was conducted through document analysis, using content analysis techniques grounded in Sigmund Freud's personality dynamics theory. The analysis reveals Olivia's evolving personality beginning with her life instincts driven by survival and emotional needs. Her anxieties are primarily realistic and neurotic, indicating a dependence on temporary defense mechanisms. Ultimately, Olivia integrates her innate personality traits (given) with self-developed characteristics (willed), reflecting her dynamic personal growth.